Efectividad agronómica y económica de la fertilización líquida y granulada en maní (Arachis hypogaea L.) en el valle del río Carrizal - Loza Delgado, John Estiven (2024)
The objective of the research was to evaluate the agronomic and economic effectiveness of liquid and granulated fertilization in peanut cultivation in the Carrizal River valley. The research was carried out at the experimental campus of the Manuel Félix López Higher Polytechnic Agricultural School of Manabí. The treatments evaluated were injected liquid fertilization (T1), liquid fertilization in drench (T2), granulated fertilization incorporated into the soil (T3), granulated fertilization in a surface band (T4) and control treatment without fertilization (T5). The main variables recorded were grain yield (GR), agronomic efficiency of NPK (EA NPK) and economic profitability (RE). The results showed significant statistical differences (p<0.05) of the treatments on the RG, where treatments T1, T2, T3 and T4 exceeded the RG of treatment T5 with 33.14, 32.83, 35.04 and 28.19%. Granular fertilization incorporated into the soil achieved the highest EA of NPK. Injected and surface drenched liquid fertilizations achieved the greatest economic advantages, with a profitability of 53 and 58%, respectively. It is concluded that under dryland conditions of the Carrizal River valley, liquid and granulated fertilizations incorporated into the soil are more convenient in peanut cultivation.